2005
DOI: 10.1007/s00122-005-2018-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic cloning and linkage mapping of the Mal d 1 (PR-10) gene family in apple (Malus domestica)

Abstract: Fresh apples can cause birch pollen-related food allergy in northern and central European populations, primarily because of the presence of Mal d 1, the major apple allergen that is cross-reactive to the homologous and sensitizing allergen Bet v 1 from birch. Apple cultivars differ significantly in their allergenicity. Knowledge of the genetic basis of these differences would direct breeding for hypoallergenic cultivars. The PCR genomic cloning and sequencing were performed on two cultivars, Prima and Fiesta, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 36 publications
4
105
0
Order By: Relevance
“…Therefore, the results have to be seen as convergent indications of the probable involvement of epistasis in fire blight resistance in apple. Interestingly, the region identified three times on LG16 also co-localizes with a gene cluster for pathogenesis-related proteins of the PR10 family (Gao et al 2005). Such genes can be considered to be candidate genes putatively involved in the control of fire blight.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the results have to be seen as convergent indications of the probable involvement of epistasis in fire blight resistance in apple. Interestingly, the region identified three times on LG16 also co-localizes with a gene cluster for pathogenesis-related proteins of the PR10 family (Gao et al 2005). Such genes can be considered to be candidate genes putatively involved in the control of fire blight.…”
Section: Discussionmentioning
confidence: 96%
“…Recent data indicated that a Pru p 1.01 isoform, named Pru p 1.06D according to its sequence identity (Gao et al, 2005;Chen et al, 2008), is one of the most abundantly expressed genes among the ripe peach mesocarp transcriptome (Trainotti et al, 2006). Pru p 1.06D shows high sequence identity (73%) to Pru p Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…They are the same cultivars that had been chosen for mapping Mal d 1 (Gao et al 2005a) and Mal d 3 (Gao et al 2005b). Two primer pairs located in the untranslated region (UTR) were used to amplify the targeted Mal d 2 genomic sequences (Table 1).…”
Section: Gene Annotationmentioning
confidence: 99%